Sizing verification of a 4kWp retrofitted grid-connected photovoltaic system: a case study in Shah Alam, Malaysia - F.A.M. Shukor; H. Zainuddin; A. Manja; F. L. M. Khir (Institute of Advanced Engineering and Science, 2020)
Electricity are commonly generated from several types of energy resources such as fossil and nuclear energy. However, due to emission of carbon dioxide from both sources, renewable energy is introduced to provide a clean and secure sustainable energy. One of the potential renewable energy application is Photovoltaic (PV) system; namely grid-connected photovoltaic (GCPV) system and stand-alone photovoltaic (SAPV) system. In this study, a mathematical approach of SEDA’s GCPV sizing model is implemented to size a 4kWp of a retrofitted GCPV system by the method claimed to be the best practice mathematical design model under tropical climate Malaysia. The outcome of the sizing approach will then be evaluated with HelioScope software, one of commercial simulation tools available in current market. The final result obtained from both methods shows that the final PV array configuration is 1 x 12 (parallel x series) which is in agreement to the actual installed system.